4-Abstracts Communications Orales -Imagerie Oncologique_ JRANF 2024_JAIM 2024_16.3 - GARBA MN; MAHAMANE AY; Joshua TAMBE; Yannick ONANA; MOUSSA ISSOUFOU Djibrillou; Adjirata KOAMA; Bénilde Marie-Ange TIEMTORE–KAMBOU; MOUSSA ISSOUFOU Djibrillou; MOBIMA Timothee; Christ Borel TAMBALA; et al. (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2024)
4-Abstracts Communications Orales -Imagerie Oncologique_ JRANF 2024_JAIM 2024_16.3